2021
DOI: 10.1007/s12630-020-01898-9
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative neurophysiologic monitoring in idiopathic scoliosis surgery: a retrospective observational study of new neurologic deficits

Abstract: Purpose Patients with adolescent idiopathic scoliosis undergoing corrective surgery are at risk for iatrogenic spinal cord injury and subsequent new neurologic deficits (NNDs). Intraoperative neurophysiologic monitoring (IONM) has been used to identify spinal cord injury; however, available data showing that IONM leads to improved clinical outcomes are inconclusive. This exploratory study aimed to examine the incidence of NNDs after idiopathic scoliosis surgery in two pediatric institutions in Canada with a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
10
0
2
Order By: Relevance
“…Nassef et al conducted a retrospective exploratory study to examine the incidence and severity of NNDs after idiopathic scoliosis surgery with a focus on IONM use. 12 In addition, they compared the incidence of NND before and after the implementation of IONM. They reviewed the charts of 547 patients aged 10-18 years old from two large tertiary pediatric centers; of these, 359 patients were monitored by IONM and 186 patients were monitored by wake-up test (Pre IONM).…”
Section: Intraoperative Neurophysiologic Monitoring During Scoliosis ...mentioning
confidence: 99%
“…Nassef et al conducted a retrospective exploratory study to examine the incidence and severity of NNDs after idiopathic scoliosis surgery with a focus on IONM use. 12 In addition, they compared the incidence of NND before and after the implementation of IONM. They reviewed the charts of 547 patients aged 10-18 years old from two large tertiary pediatric centers; of these, 359 patients were monitored by IONM and 186 patients were monitored by wake-up test (Pre IONM).…”
Section: Intraoperative Neurophysiologic Monitoring During Scoliosis ...mentioning
confidence: 99%
“…In this issue of the Journal, Nassef et al reported a retrospective before-and-after study to compare the effect of the Stagnara wake-up test with evoked potentials (EP) monitoring on postoperative neurologic deficits in 547 adolescent patients (10-18 yr old) who underwent scoliosis correction surgery in two Canadian institutions between 2007 and 2014. 6 Both institutes transitioned their neurologic monitoring technique from the Stagnara wakeup test to EP monitoring around 2009/2010. In their analysis, the authors found that the patients who received intraoperative neuromonitoring were less likely to develop postoperative neurologic deficits compared with those who underwent the Stagnara wake-up test (odds ratio, 0.39; 95% confidence interval, 0.18 to 0.86; P = 0.020).…”
mentioning
confidence: 99%
“…The authors concluded multimodal intraoperative neuromonitoring (SSEPs and MEPs) is associated with reduced overall incidence of new neurologic deficits, although they were not able to adjust for confounding variables. 6 Given the paucity of evidence describing the role of neurologic monitoring and neurologic outcomes in spine surgery, the authors should be commended for undertaking this study and sharing their experience. This study represents one of very few cohorts in the literature in which a direct head-tohead outcome comparison was made between these two intraoperative neurologic monitoring techniques in scoliosis surgery.…”
mentioning
confidence: 99%
See 2 more Smart Citations